2017
DOI: 10.2486/indhealth.2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the effects of poor health and low income on early retirement: a systematic review and meta-analysis

Abstract: The main aim of this study was to estimate the effects of poor health and low income on early retirement. For this purpose systematic review and meta-analysis were conducted. Web of Science, PUBMED and Scopus databases were searched systematically. Finally 17 surveys were added in meta-analysis. These studies were conducted in 13 countries. At the end a Meta regression was done to show the effects of welfare system type on effect sizes of poor health and low income. The results of this study showed that poor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(45 reference statements)
1
2
1
Order By: Relevance
“…This finding may reflect a healthy worker effect, whereby healthy persons are more likely to work beyond retirement, and unhealthy persons are more likely to exit from the workforce. 67–71 Unlike our result, a previous systematic review by Shim et al 30 found mixed results on the association between on-time retirement and mortality, meaning that some included studies found no effect or a lower risk of mortality for those retiring on time. However, the authors included studies that used the general population as a reference group to examine this association, and it is well known that the general population has higher mortality rates compared with the working population, especially compared with those working beyond retirement.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding may reflect a healthy worker effect, whereby healthy persons are more likely to work beyond retirement, and unhealthy persons are more likely to exit from the workforce. 67–71 Unlike our result, a previous systematic review by Shim et al 30 found mixed results on the association between on-time retirement and mortality, meaning that some included studies found no effect or a lower risk of mortality for those retiring on time. However, the authors included studies that used the general population as a reference group to examine this association, and it is well known that the general population has higher mortality rates compared with the working population, especially compared with those working beyond retirement.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, by November/December 2020, people may have realised that the pandemic would last longer than expected, and started to adapt to a 'new normal' (Corpuz 2021), so changes in retirement plans of healthier adults were not pronounced. However, poor self-rated health was associated with a lower possibility of delaying retirement, consistent with the literature that poor health pushes people out of their jobs (Mein et al 2000;Homaie Rad et al 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Studies have shown that during the COVID-19 pandemic, financial insecurity or concerns led to the deterioration of mental health worldwide (Wilson et al 2020;Cheng et al 2021;De Miquel et al 2022). Following an adaptation of the model proposed by Homaie Rad et al (2017), there exists a trade-off between the direct effect of financial insecurity on retirement and the indirect effect via health factors. When the positive utility of financial security is larger than the negative utility of poor physical or mental health, later retirement plans may be made.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, the prevalence of chronic disease increases with age, 46% of workers aged 55–64 years reported at least one chronic disease in 2018 [9]. It is widely known that poor health and chronic diseases are associated with early exit from work (e.g., in [10]). Early retirement has been shown to be a good alternative for workers with chronic disease when continuation of work is no longer possible [11].…”
Section: Discussionmentioning
confidence: 99%